2019
DOI: 10.1002/fsn3.1184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conditioner and moisture content on flowability of yellow cornmeal

Abstract: Flow characterization of ground materials based on standard physical properties is not always accurate and must be complemented with other properties that help characterize their flowability. The flow properties of yellow cornmeal as a function of moisture content (10.0%, 13.5% 17.0%, and 20.0% wet basis) and concentrations of added conditioner (calcium stearate, a caking agent classified at GRAS, at 0.50%, 0.75%, and 1.00% wt/wt) were measured. The optimum flow behavior characteristics of the cornmeal were ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…Carr's index of 6 suggested that the powder was in the category of excellent flowability, while the Hausner ratio of 1.16 revealed that it can be categorized as powder with good flowability (Chinwan & Castell‐Perez, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Carr's index of 6 suggested that the powder was in the category of excellent flowability, while the Hausner ratio of 1.16 revealed that it can be categorized as powder with good flowability (Chinwan & Castell‐Perez, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Esta situación, permite clasificar el material entre polvos con fluidez intermedia y polvos con dificultades para fluir libremente. Por otro lado, el análisis de fluidez a partir del seguimiento al AR presentó una fluctuación entre los intervalos 21,3 ± 0,8 -38,7 ± 1,1°, lo cual corresponde a una variabilidad desde excelente fluidez (AR<25) hasta fluidez intermedia a pobre (AR>25)(Chinwan & Castell-Perez, 2019).…”
unclassified
“…It was determined that while the Hausner ratio of samples was 1.28–1.44, Carr index values were between 21.71 and 30.34%. It was evaluated that the honey powder samples had passable and poor flow properties according to the Hausner ratio and Carr index classifications (Chinwan and Castell-Perez, 2019) and the increasing concentration of pollen in the mixture improved the flow properties of the samples because of reducing the Hausner ratio and Carr index values. It was reported that powder flowability is influenced by moisture content and particle size and distribution (Samborska, 2019).…”
Section: Resultsmentioning
confidence: 99%